2011
DOI: 10.1175/2010jcli3749.1
|View full text |Cite
|
Sign up to set email alerts
|

Observed Increase of TTL Temperature and Water Vapor in Polluted Clouds over Asia

Abstract: Satellite observations are analyzed to examine the correlations between aerosols and the tropical tropopause layer (TTL) temperature and water vapor. This study focuses on two regions, both of which are important pathways for the mass transport from the troposphere to the stratosphere and over which Asian pollution prevails: South and East Asia during boreal summer and the Maritime Continent during boreal winter. Using the upper-tropospheric carbon monoxide measurements from the Aura Microwave Limb Sounder as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…Temperature increases by ∼ 1-5 K near the tropical tropopause. A similar increase in temperature is reported by , , Liu et al (2009), andSu et al (2011). The interior of the anticyclone over the Tibetan Plateau experiences a significant warming as well.…”
Section: Impact Of Aerosols On Temperature Water Vapour and Circulasupporting
confidence: 79%
See 2 more Smart Citations
“…Temperature increases by ∼ 1-5 K near the tropical tropopause. A similar increase in temperature is reported by , , Liu et al (2009), andSu et al (2011). The interior of the anticyclone over the Tibetan Plateau experiences a significant warming as well.…”
Section: Impact Of Aerosols On Temperature Water Vapour and Circulasupporting
confidence: 79%
“…Observations and modelling studies suggest that the occurrence of aerosol layers near the tropopause could strongly affect the formation of cirrus clouds and precipitation (Li et al, 2005;Yin et al, 2005;Su et al, 2011). Liu et al (2009) reported that the homogeneous freezing of SO 2− 4 particles dominates cirrus cloud formation in the upper troposphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A simulation study showed that variations in transport explain 30% of the lower SWV changes over the past several decades (Tian and Chipperfield 2006). In particular, the upward transport in the Asian summer monsoon is thought to be capable of transporting a large amount of water vapour into the stratosphere (Gettelman et al 2004;Fu et al 2006;Su et al 2011;Bian et al 2011Bian et al , 2012. As volcanic eruptions can change the tropopause temperature and bring tropospheric water vapour into the stratosphere, SWV can increase significantly after such eruptions (Considine et al 2001;Joshi and Jones 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the transport of surface emissions into the tropospheric atmosphere is strong influenced by many factors, e.g., topography (Fu et al 2006;Su et al 2011), convective overshooting (Sun and Huang 2015), and "Tape-recorder" (Liu et al 2007;Jiang et al 2015). Because topography and thermal characteristics vary between different regions, the transport of chemical compounds and aerosols horizontally in the troposphere and vertically from the troposphere into the stratosphere is also variable Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%